From cheese whey permeate to Sakacin-A/bacterial cellulose nanocrystal conjugates for antimicrobial food packaging applications: a circular economy case study - Manuela Rollini (Nature Portfolio, 2020)
Abstract Applying a circular economy approach, this research explores the use of cheese whey permeate (CWP), by-product of whey ultrafiltration, as cheap substrate for the production of bacterial cellulose (BC) and Sakacin-A, to be used in an antimicrobial packaging material. BC from the acetic acid bacterium Komagataeibacter xylinus was boosted up to 6.77 g/L by supplementing CWP with β-galactosidase. BC was then reduced to nanocrystals (BCNCs, 70% conversion yield), which were then conjugated with Sakacin-A, an anti-Listeria bacteriocin produced by Lactobacillus sakei in a CWP based broth. Active conjugates (75 Activity Units (AU)/mg), an innovative solution for bacteriocin delivery, were then included in a coating mixture applied onto paper sheets at 25 AU/cm2. The obtained antimicrobial food package was found effective in reducing Listeria population in storage trials carried out on a fresh Italian soft cheese (named “stracchino”) intentionally inoculated with Listeria. Production costs of the active material have been mainly found to be associated (90%) to the purification steps. Setting a maximum prudential 50% cost reduction during process up-scaling, conjugates coating formulation would cost around 0.89 €/A4 sheet. Results represent a practical example of a circular economy production procedure by using a food industry by-product to produce antimicrobials for food preservation.